Strategy For Increasing The Competitiveness of Mulur Rice Product Trought SWOT Analysis (Case Study : Mulur, Sukoharjo). - Purnaningsih, Sri; Alasimi, Nadina Hajar; Safira, Safira (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This study, titled “Strategi Peningkatan Daya Saing Produk Beras Mulur melalui Analisis SWOT,” aims to analyze the competitive position of Beras Mulur and propose strategic measures to enhance its market competitiveness. The research employs a SWOT analysis framework, combining quantitative and qualitative approaches to evaluate internal and external factors affecting the product. Data collection methods include surveys, interviews, and documentation, with a purposive sampling of key stakeholders such as farmers, distributors, and consumers. The findings indicate that Beras Mulur possesses significant strengths, including superior quality and competitive pricing, while facing challenges such as limited product diversification and underdeveloped marketing strategies. Opportunities exist in the form of growing consumer preference for local products and the expanding digital market, though threats from imported competitors and fluctuating raw material prices persist. The research concludes that strategic initiatives, such as digital marketing, product diversification, and leveraging government support, are essential to improving the product's competitive edge. By addressing weaknesses and mitigating threats, Beras Mulur can strengthen its market position and achieve sustainable growth. This study contributes to the literature on agribusiness strategy and offers practical recommendations for local product development.